Lessons learned from the PMTCT program in Swaziland: challenges with accepting lifelong ART for pregnant and lactating women - a qualitative study - Leila Katirayi; Caspian Chouraya; Kwashie Kudiabor; Mohammed Ali Mahdi; Mary Pat Kieffer; Karen Marie Moland; Thorkild Tylleskar (BMC, 2016)
Abstract Background Swaziland has one of the highest HIV prevalence rates in sub-Saharan Africa, 26 % of the adult population is infected with HIV. The prevalence is highest among pregnant women, at 41.1 %. According to Swaziland's prevention of mother-to-child transmission (PMTCT) guidelines, approximately 50 % of pregnant women are eligible for antiretroviral therapy (ART) by CD4 criteria (<350 cells/ml). Studies have shown that most mother-to-child transmission and postnatal deaths occur among women who are eligible for ART. Therefore, ensuring that ART eligible women are initiated on ART is critical for PMTCT and for mother and baby survival. This study provides insight into the challenges of lifelong ART initiation among pregnant women under Option A in Swaziland. We believe that these challenges and lessons learned from initiating women on lifelong ART under Option A are relevant and important to consider during implementation of Option B+. Methods HIV-positive, treatment-eligible, postpartum women and nurses were recruited within maternal and child health (MCH) units using convenience and purposive sampling. Participants came from both urban and rural areas. Focus group discussions (FGDs) and structured interviews using a short answer questionnaire were conducted to gain an understanding of the challenges experienced when initiating lifelong ART. Seven FGDs (of 5-11 participants) were conducted, four FGDs with nurses, two FGDs with women who initiated ART, and one FGD with women who did not initiate ART. A total of 83 interviews were conducted; 50 with women who initiated ART and 33 with women who did not initiate. Data collection with the women was conducted in the local language of SiSwati and data collection with the nurses was done in English. FGDs were audio-recorded and simultaneously transcribed and translated into English. Analysis was conducted using thematic analysis. Transcripts were coded by two researchers in the qualitative software program MAXqda v.10. Thematic findings were illustrated using verbatim quotes which were selected on the basis of being representative of a specific theme. The short-answer interview questionnaire included specific questions about the different steps in the woman's experience initiating ART; therefore the responses for each question were analyzed separately. Results Findings from the study highlight women feeling overwhelmed by the lifetime commitment of ART, feeling "healthy" when asked to initiate ART, preference for short-course prophylaxis and fear of side effects (body changes). Also, the preference for nurses to determine on an individual basis the number of counseling appointments a woman needs before initiating ART, more information about HIV and ART needed at the community level, and the need to educate men about HIV and ART. Conclusion Women face a myriad of challenges initiating lifelong ART. Understanding women's concerns will aid in developing effective counseling messages, designing appropriate counseling structures, understanding where additional support is needed in the process of initiating ART, and knowing who to target for community level messages.